Application of screening using a flip-flow screen and shallow groove dense-medium separation in a steam coal preparation plant. Issue 8 (3rd August 2022) - Chen, Zengqiang; Huang, Long; Jiang, Haishen; Zhao, Yuemin; Liu, Chusheng; Duan, Chenlong; Zhang, Bo; Yang, Guangrong; Chai, Jin; Ban, Haijun; Yu, Shijie; Wu, Jida
ABSTRACT: Low-rank steam coal is an important coal resource, but has high water and ash content, which needs to be separated to improve its quality and calorific value. In this paper, the process of screening using a flip-flow screen and density separator using a shallow groove dense-medium separator for steam coal was proposed and applied to the Lijiahao coal preparation plant. Kinematics of the screen box and the surface of the flip-flow screen were investigated using an acceleration and laser displacement measurement and analysis system. The mechanism of the flip-flow screen to overcome aperture blocking and to enhance the screening performance for moist and fine coal was discussed. The results from an industrial experiment when screening at 3 mm showed that the screening efficiency was 82.51%, while the total misplaced materials were 5.91%. The commercial separation of a wide size range of coal using a shallow groove dense-medium separator was analyzed. The results showed that the system exhibited satisfactory separation performance for 100–3 mm coal, whereas the corresponding Ep value was found to be 0.06 g/cm 3 . Compared with the 6 mm separation system, the yield of clean coal increased by 8.50%, which remarkably increased the economic benefits for the company.